Output volatility and efficiency gains: Evidence from Latin American gross value added - Kurt Hafner (Journal of Applied Economics, 2021)
Based on gross value added (GVA) shares of economic activities from 1990 to 2014, the paper shows that convex growth-instability frontiers exist for 19 Latin American countries. Numerical simulations show that in 2011, Latin America's industry portfolios were below Markowitz's efficiency frontier, and that rearranging the shares of economic activities contributes to efficiency gains that are negatively linked to industrial diversification. Reducing output volatility, MERCOSUR countries with a low degree of industrial diversification would average relatively high efficiency gains, while the reverse is true for CACAM and CAN countries. Analyzing more recent industry portfolios, Latin American countries closed the efficiency frontier gap and captured efficiency gains in terms of lower output volatility and higher GVA growth rates. Convex growth-instability frontiers are confirmed by stochastic frontier analysis, which identifies variations in employment ratios and industrial diversification as the key sources of inefficiency.
Keywords: 330; Economic activities; regional growth; economic instability; portfolio theory; stochastic frontier analysis